Balance sheet effects in currency crises: Evidence from Brazil - Marcio Magalh\~aes Janot; Márcio Gomes Pinto Garcia; Walter Novaes (EconomiA, 2021)
In third generation currency crises models, balance sheet losses from currency depreciations propagate the crises into the real sector of the economy. To test these models, we built a firm-level database that allowed us to measure currency mismatches around the 2002 Brazilian currency crisis. We found that between 2001 and 2003, firms with large currency mismatches just before the crisis reduced their investment rates 8.1 percentage points more than other publicly held firms. We also showed that the currency depreciation increased exporters revenue, but those with currency mismatches reduced investments 12.5 percentage points more than other exporters. These estimated reductions in investment are economically very significant, underscoring the importance of negative balance sheet effects in currency crises.
Keywords: F32; F34; G31; G32; 330; Investment; Currency mismatches; Currency crises; Hedge; Financial constraints